Construction of the originality criterion for AIGC - LI Yiheng; ZHANG Zheng (大数据)
With the popularization of generative artificial intelligence technology, the issue of copyright for AIGC is highlighted. The originality criterion under traditional “instrumental theory” and “contribution theory” is particularly inadequate when it is applied to AIGC, and it is necessary to construct more actionable originality criterion. By analyzing the legislative value of copyright law and empirical research on the norms of current laws, combined with empirical research on domestic and foreign judicial cases, the construction of originality criterion under “determinism” was proposed. Based on anthropocentrism, adhered to the uniqueness of the copyright subject, regarded labor input as the basis of rights, and the causal relationship theory in Anglo-American law system was introduced, which took the determination of the presentation results of human works and the control of the creative process as sufficient and necessary conditions. Thus, determinism is self-consistent in terms of objects, standards, laws, facts, and causal relationships, and can guide practical application.